A Nanosheet Array of Cu2Se Intercalation Compound with Expanded Interlayer Space for Sodium Ion Storage. Issue 25 (30th April 2020) - Xiao, Yuanhua; Zhao, Xiaobing; Wang, Xuezhao; Su, Dangcheng; Bai, Shuo; Chen, Wei; Fang, Shaoming; Zhou, Liming; Cheng, Hui‐Ming; Li, Feng
Abstract: Intercalation chemistry/engineering has been widely investigated in the development of electrochemical energy storage. Graphite, as an old intercalation host, is receiving vigorous attention again via a new halogen intercalation. Whereas, exploiting new intercalation hosts and optimizing the intercalation effect still remains a great challenge. This study fabricates a Cu2 Se intercalation compound showing expanded interlayer space and nanosheet array features by using a green growth approach, in which cetyltrimethyl ammonium bromide (CTAB) is inserted into Cu2 Se at an ambient temperature. When acting as an electrode material for sodium‐ion batteries, the Cu2 Se–CTAB nanosheet arrays exhibit excellent discharge capacity and rate capability (426.0 mAh g −1 at 0.1 A g −1 and 238.1 mAh g −1 at 30 A g −1 ), as well as high capacity retention of ≈90% at 20 A g −1 after 6500 cycles. Benefiting from the porous array architecture, the transport of electrolytes is facilitated on the surface of Cu2 Se nanosheets. In particular, the CTAB intercalated in the interlayer space of Cu2 Se can increase its buffer space, stabilize the polyselenide shuttle, and prevent the fast growth of Cu nanoparticles during its electrochemical process. Abstract : A nanosheet array of Cu2 Se intercalation compounds with expanded interlayer space is directly grown on Cu foil by the insertion of cetyltrimethyl ammonium bromide (CTAB) at room temperature. The CTAB inserted in the interlayer space provides buffer space for electrochemical volume expansion, confines the fast growth of Cu metal particles and restricts the shuttling of polyselenide intermediates.